2016
DOI: 10.1007/s00423-016-1428-x
|View full text |Cite
|
Sign up to set email alerts
|

Change of initial and ICU treatment over time in trauma patients. An analysis from the TraumaRegister DGU®

Abstract: The reduction LOS in the analyzed dataset is mainly explained by the relevantly reduced rate of patients being intubated at the time of ICU admission. Our data demonstrate that trauma patients' in-hospital course is influenced by reduced intubation rate at the time of ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
3
0
4
Order By: Relevance
“…Findings reporting on mechanical ventilation time are contradictory. While some authors did not find changes with regard to mechanical ventilation time [ 43 , 44 ], Probst et al described a decrease from 11.6 days to 8.7 days during a 30 year observation period [ 45 ]. However, the majority of data are derived from general trauma populations, which were not adjusted for patients with severe chest trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Findings reporting on mechanical ventilation time are contradictory. While some authors did not find changes with regard to mechanical ventilation time [ 43 , 44 ], Probst et al described a decrease from 11.6 days to 8.7 days during a 30 year observation period [ 45 ]. However, the majority of data are derived from general trauma populations, which were not adjusted for patients with severe chest trauma.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the severity of pulmonary contusion correlates with the development of pulmonary infections, respiratory failure, sepsis, MOF, and mortality [4, 28]. Böhmer et al have recently published an analysis of changes of ICU treatment over a period of 10 years [29] . This study confirmed a general trend towards reduced ventilation time and shorter stay in ICU as well.…”
Section: Discussionmentioning
confidence: 99%
“…6 La tendencia en el mundo es que la atención de estos pacientes incluye la necesidad de procedimientos quirúrgicos y/o ingreso a Unidades de Cuidado Intensivo (UCI) ha cambiado a través de los años optimizando los recursos, más pacientes requieren menos días de ventilación o estancia, menores complicaicones, realizando una mejor evaluación de los pacientes con ayudas diagnósticas, mejorando las condiciones desde la sala de emergencias a cirugía con la reanimación. 10,11 Por ello, es pertinente describir las características de los pacientes politraumatizados que requirieron UCI que poco se ha descrito en Colombia para lograr identificar desde el ingreso a urgencias, cuáles son los que la requerirán.…”
Section: 5005/jp-journals-10030-1196unclassified